Implications of Using Illegal Drugs in the Increase of Criminality at Bagong Silang Caloocan City.: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Illegal Drugs have been part of our society for a long period of time, But suddenly, it is illegallyabused by those people who only have interests for their own sake, and to fulfill theirsatisfaction as a result of using illegal drugs affects their mind and their way of thinking so theyresult from committing crimes. Using illegal drugs has many negative effects on our bodies.Substance abuse and mental health are linked because the psychological effects of drugaddiction cause changes in your body and brain. From an outside perspective, someone withdrug addiction looks like they are repeatedly making bad choices and ignoring reasons thatmay result in drug-related crimes as they are not aware of what they are doing and whatmaybe the effect of their bad decisions caused by taking or dealing drugs. Using Illegal drugsshows some negative effects that can affect not only the people using it. It can also affect thepeople in his/ her surroundings.The results of the study about the implications of using illegal drugs in the increase ofcriminality at Bagong Silang, Caloocan City, indicate that while an individual is under theinfluence of drugs, there is a high chance that that individual might commit a crime becausedrugs affect his/her way of thinking and altered the reasoning of an individual. The researchersuggests some preventive measures on how the police and barangay might lessen thecriminality because of using illegal drugs.The study also revealed that the respondents “Strongly Agree” that Drugs are one of theimplications of the increase in criminality in Bagong Silang, Caloocan City. The study alsorecommended that groups of people or organizations help individuals who are using illegaldrugs to cope with their problems and provide a better solution. The researchers recommendconducting seminars and programs about the negative effects of illegal drugs on an individualand how can the use of illegal drugs lead to an increase in criminality, and also to strengthenthe security in the community to prevent the commission of crime because of using illegaldrugs.
Keywords: Criminology